2017
DOI: 10.3390/ijms18061176
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic In Vivo Profiling of DNA Damage and Repair after Radiotherapy Using Canine Patients as a Model

Abstract: Time resolved data of DNA damage and repair after radiotherapy elucidates the relation between damage, repair, and cell survival. While well characterized in vitro, little is known about the time-course of DNA damage response in tumors sampled from individual patients. Kinetics of DNA damage after radiotherapy was assessed in eight dogs using repeated in vivo samples of tumor and co-irradiated normal tissue analyzed with comet assay and phosphorylated H2AX (γH2AX) immunohistochemistry. In vivo results were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…To evaluate the damage to B16-BL6 melanoma cells, we measured DSBs in the cell by γH2AX. γH2AX is known as a marker of DSBs within chromatin and to increase the relative intensity with an increase in the radiation dose [28,29]. Figure 5A displays fluorescence-labeled γH2AX in the nuclei of melanoma cells, and Figure 5B illustrates the signal intensity of fluorescence-labeled γH2AX.…”
Section: Ppix Enhances Cellular Damage With Dsbs By X-ray Irradiationmentioning
confidence: 99%
“…To evaluate the damage to B16-BL6 melanoma cells, we measured DSBs in the cell by γH2AX. γH2AX is known as a marker of DSBs within chromatin and to increase the relative intensity with an increase in the radiation dose [28,29]. Figure 5A displays fluorescence-labeled γH2AX in the nuclei of melanoma cells, and Figure 5B illustrates the signal intensity of fluorescence-labeled γH2AX.…”
Section: Ppix Enhances Cellular Damage With Dsbs By X-ray Irradiationmentioning
confidence: 99%
“…For example, with γ = 10 h −1 (the upper boundary of this parameter), repair proteins reactivate very quickly from the irradiation event; the repair probability recovers to 94% 30 min post irradiation. This is unrealistically high given the typical delays observed experimentally (see Figure 4 and [ 38 ]). Since no prior information is available on a given parameter values' positions within the search space [ a ; b ], uniform prior distributions with boundaries a and b , 𝒰 [ a ; b ], are chosen.…”
Section: Methodsmentioning
confidence: 90%
“…Clonogenic cell survival and comet assay measurements were shown to be repeatable [14,29]; thus, it is reasonable to expect repeatable results from patient biopsies [38]. This Figure 6: Histograms of parameter values after calibration with the software set to different modes, and at the bottom, the joint distribution obtained by combining the two posterior sets is shown.…”
mentioning
confidence: 86%
“…Contrary to the widespread use in clinical studies, γH2AX detection in in vivo non-clinical studies has not been reported. Apart from its use in clinical drug development, γH2AX was reported to be a useful bio-dosimeter in fundamental radiotherapy research in rhesus macaques [ 28 ] and in canines [ 29 ], which clearly suggests that γH2AX is available for use in experimental animal models. Since the clinical studies and experiments in large-animal models commonly use peripheral lymphocytes or leukocytes as target cells for γH2AX evaluation, the small volume of blood that is sampled in rodent models might be a limitation in non-clinical models.…”
Section: Use Of γH2ax In Non-clinical Studiesmentioning
confidence: 99%